ITEM ANALYSIS OF MULTIPLE-CHOICE QUESTIONS: AN ASSESSMENT OF YOUNG LEARNERS - Maya Marsevani (English Review: Journal of English Education, 2022)
Although English has been taught for decades in Indonesia, the quality of multiple-choice question given to young learners was hardly examined. To touch on the issue, this study aims at determining the quality of 10 multiple-choice questions (MCQs) in a public elementary school in terms of difficulty level (P), discrimination power (D), and distractor efficiency (DE). This study employed a cross-sectional study to obtain information and evaluate MCQs in the students’ tests. It was found the multiple-choice items were efficient in which 80% of them have acceptable difficulty and 20% of them were fairly easy (P > 70%). The discrimination index of 8 (80%) items was excellent and 2 of the MCQs were good. Among 40 distractors, 32 (80%) of them were functional distractors while 8 of them were non-functional distractors (NFDs). It can be concluded that most of the difficulty index was acceptable, the items discrimination power was good. In terms of distractor efficiency, two items were completely inefficient. Furthermore, MCQs that are considered poor should be revised, re-tested, and reviewed before incorporating them into the future test. This study hopefully encourages teachers to identify poorly developed MCQs and to improve their quality.